Electrocardiographic and Echocardiographic Parameters in Pega Breed Donkeys: A Descriptive Study - Cruz-Aleixo, Amanda Sarita [UNESP]; de Oliveira, Karina Cristina [UNESP]; de Oliveira Ferreira, Lucas Vinícius [UNESP]; Cedeo Quevedo, Dario Alejandro; Cruz, Raíssa Karolliny Salgueiro; Tsunemi, Miriam Harumi [UNESP]; Chiacchio, Simone Biagio [UNESP]; Lourenço, Maria Lucia Gomes [UNESP] (MDPI, 2023)
Clinical, electrocardiographic and echocardiographic parameters in Pega donkeys are scarce in the literature; hence, this study was performed to describe the echocardiographic and electrocardiographic measurements in Pega breed donkeys. The objectives of this study were to describe and illustrate the clinical, electrocardiographic, and echocardiographic parameters in Pega donkeys used for reproduction. Fifty Pega breed donkeys were evaluated, with an average age of 3.4 years and with 20 males and 30 females. In each animal, the electrocardiographic examination at rest was performed using the TEB® computerized system, and the echocardiographic examination was performed using an ultrasound device with a Doppler function multifrequency sectorial transducer in 2D mode (Sonosite® M turbo). Standardizing the electrocardiographic and echocardiographic parameters for the Pega breed donkey can contribute to future assessments regarding possible changes that excessive effort can promote in these parameters to a management engrossed on animal welfare.
Keywords: donkeys; echocardiogram; electrocardiogram; equine; heart